Endothelial Dysfunction and Passive Changes in the Aorta and Coronary Arteries of Diabetic db/db Mice - Beck, Lilliana; Su, Junjing; Comerma-Steffensen, Simon; Pinilla, Estéfano; Carlsson, Rune; Hernanz, Raquel; Sheykhzade, Majid; Danielsen, Carl Christian; Simonsen, Ulf (Frontiers in Physiology, 2020)
Endothelial cell dysfunction and vessel stiffening are associated with a worsened prognosis in diabetic patients with cardiovascular diseases. The present study hypothesized that sex impacts endothelial dysfunction and structural changes in arteries from diabetic mice. In diabetic (db/db) and normoglycemic (db/db+) mice, the mechanical properties were investigated in pressurized isolated left anterior descending coronary arteries and aorta segments that were subjected to tensile testing. Functional studies were performed on wire-mounted vascular segments. The male and female db/db mice were hyperglycaemic and had markedly increased body weight. In isolated aorta segments without the contribution of smooth muscle cells, load to rupture, viscoelasticity, and collagen content were decreased suggesting larger distensibility of the arterial wall in both male and female db/db mice. In male db/db aorta segments with smooth muscle cell contribution, lumen diameter was smaller and the passive stretch-tension curve was leftward-shifted, while they were unaltered in female db/db aorta segments versus control db/db+ mice. In contrast to female db/db mice, coronary arteries from male db/db mice had altered stress-strain relationships and increased distensibility. Transthoracic echocardiography revealed a dilated left ventricle with unaltered cardiac output, while aortic flow velocity was decreased in male db/db mice. Impairment of acetylcholine relaxation was aggravated in aorta from female db/db compared to control and male db/db mice, while impairment of sodium nitroprusside relaxations was only observed in aorta from male db/db mice. The remodeling in the coronary arteries and aorta suggests an adaptation of the arterial wall to the reduced flow velocity with sex-specific differences in the passive properties of aorta and coronary arteries. The findings of less distensible arteries and more pronounced endothelial dysfunction in female compared to male diabetic mice may have implications for the observed higher incidence of macrovascular complications in diabetic women.